الموازنة المائية بين الايراد المائي والاحتياجات المائية لنهر البتيرة في محافظة ميسان - حسن شنون فلاح (Al-Adab Journal, 2018)
Abstract The Alaptarh River, the largest river water network to the province of Missan in southern Iraq in terms of drainage and the length is divided from the right bank of the Tigris River north of the city of Amara at about 18 km, with a length of at the present time (56) km after it was 76 km before draining of the marshes operations, characterized by surface area being the full Banbsat resulting from the nature of its geological structure as well as the sediment carried by rivers. Altitude region between (6-11) m above sea level , and this fact is reflected on the slow surface slope where, as it does not exceed the rate of regression (6.25) cm / km towards the north-south . the consequence of this regression Alaptarh river flow in the same direction . River going through areas populated rural and urban, from the most important spend al Maymunah and al Salam. River water investment and household drinking uses is limited primarily because of (4179318) m3 / year, followed by Alaanaajt water for agriculture, which amounted to (380,369) m3 / year n and finally the needs of livestock of water (165,036) m3 / year when compared to the sum of these needs annual revenue water of the River Alaptarh of (0.88) billion / m 3 for the year 2014 is clear that the water balance of the river of (875,275,277 +) m 3 / year